Mujeres al poder: una lectura de Lisístrata - García Novo, Elsa (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
The authores of th¡s essay makes a survey of The main contrapositions of characters: Lysistrata/other women. women/men (Lysistrata/npó ouXoq, married women/married rnen, oíd wornen/old men). Athenians¡Spartans, and suggests that, breakitíg the barriers wornan-man, friend-eneniy, dic cornedy lays [he foundations of a humanistic conception.